2022
DOI: 10.3389/fpls.2022.1030138
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals the proline metabolic pathway and its potential regulation TF-hub genes in salt-stressed potato

Abstract: Potato (Solanum tuberosum) is currently the third most important food crop in the world. However, the production of potato is seriously threatened by salt stress, which often occurs in the facility cultivation environment, and the mining of salt tolerance genes in potato remains to be further studied. In this study, test-tube plantlets of DM potato were treated with 200-mM NaCl to simulate salt stress, and 15 cDNA libraries were constructed for RNA-seq analysis. A total of 8383 DEGs were identified, of which 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The composition of all four treatments was based on 1/2 Hoagland nutrient solution, which included NH 4 H 2 PO 4 (0.5 mM), KNO 3 (2.5 mM), Ca(NO 3 ) 2 .4H 2 O (2.5 mM), MgSO 4 .7H 2 O (1 mM), H 3 BO 3 (23 μM), ZnSO 4 .7H 2 O (0.38 μM), CuSO 4 ·5H 2 O (0.16 μM), MnCl 2 .4H 2 O (4.5 μM), H 2 MoO 4 (0.2 μM), Fe‐EDTA (25 μM). The CK treatment solution retained the composition of 1/2 Hoagland nutrient solution; the LP treatment solution decreased the P concentration to 1/10 of the original concentration (Sung et al, 2015); the S treatment solution involved the addition of NaCl (200 mM) to the 1/2 Hoagland nutrient solution (Jing et al, 2022); LPS treatment solution also incorporated NaCl (200 mM) into the LP nutrient solution. Each treatment contains three replications.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of all four treatments was based on 1/2 Hoagland nutrient solution, which included NH 4 H 2 PO 4 (0.5 mM), KNO 3 (2.5 mM), Ca(NO 3 ) 2 .4H 2 O (2.5 mM), MgSO 4 .7H 2 O (1 mM), H 3 BO 3 (23 μM), ZnSO 4 .7H 2 O (0.38 μM), CuSO 4 ·5H 2 O (0.16 μM), MnCl 2 .4H 2 O (4.5 μM), H 2 MoO 4 (0.2 μM), Fe‐EDTA (25 μM). The CK treatment solution retained the composition of 1/2 Hoagland nutrient solution; the LP treatment solution decreased the P concentration to 1/10 of the original concentration (Sung et al, 2015); the S treatment solution involved the addition of NaCl (200 mM) to the 1/2 Hoagland nutrient solution (Jing et al, 2022); LPS treatment solution also incorporated NaCl (200 mM) into the LP nutrient solution. Each treatment contains three replications.…”
Section: Methodsmentioning
confidence: 99%
“…Different letters were used to indicate significant differences ( p < 0.05). The ggcor package was used to perform the correlation test in the R circumstance [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the proteomic level, the number of differentially regulated proteins in potatoes increased by about three-fold under salt stress, and the level of most highly abundant proteins increased, except for genes associated with photosynthesis. Jing et al [ 215 ] (2022) conducted transcriptome sequencing on potato DM plants and found 13 differentially expressed genes in the proline metabolism pathway that were correlated with increased proline content of DM plants.…”
Section: Progress Toward the Identification Of Salt Tolerance Genes I...mentioning
confidence: 99%